Drug Safety Issues in Therapy COVID-19 - D. G. Levitova; S. A. Gracheva; A. S. Samoylov; U. D. Udalov; E. A. Praskurnichiy; O. V. Parinov (SINAPS LLC, 2020)
One of the serious problems of modern Health care is a new coronavirus infection - COVID-19, which has been declared a global pandemic by the World Health Organization and has covered more than 190 countries. Despite the measures has been taken to limit contacts between people and isolate patients with suspected coronavirus infection, the number of cases grows exponentially every day. Leading laboratories are working on a vaccine, but according to some optimistic forecasts, it may be available no earlier than 11-12 months. According to published data on attempts using various drug regimens in clinical trials, methodological manuals and clinical guidelines for patient management are constantly being developed and updated depending on the severity of the condition. The appointment of a number of drug combinations should be carried out taking into account the definition of an individual assessment of the benefits and risks, because there is ample evidence of serious side effects.More serious lung tissue lesions are characteristic of patients of an older age group (over 60 years old) with the presence of concomitant diseases, such as cardiovascular, cerebrovascular, diabetes mellitus and obesity, diseases of the bronchopulmonary system and kidneys, which implies taking basic therapy in a constant mode. The appointment of a number of drug combinations should be carried out taking into account the definition of an individual assessment of the benefits and risks, because there is enough evidence of serious side effects, such as the QT interval prolongation, hepatotoxicity, adverse events from the central nervous system. It is necessary to evaluate the interaction of drugs used to treat infections caused by the COVID-19 virus with drugs used in outpatient practice.